PoRal2 Is Involved in Appressorium Formation and Virulence via Pmk1 MAPK Pathways in the Rice Blast Fungus Pyricularia oryzae - Qu, Yingmin; Wang, Jing; Huang, Pengyun; Liu, Xiaohong; Lu, Jianping; Lin, Fu-Cheng (Frontiers in Plant Science, 2021)
Pyricularia oryzae is an important plant pathogenic fungus that can severely damage rice and wheat crops, leading to significant reductions in crop productivity. To penetrate into and invade tissues of its plant host, this fungus relies on an invasive structure known as an appressorium. Appressorium formation is rigorously regulated by the cAMP-PKA and Pmk1 MAPK pathways. Here, we identified PoRal2, a homologous protein of Schizosaccharomyces pombe Ral2, and characterized its roles in fungal development and virulence in P. oryzae. PoRal2 contains N-terminal kelch repeats and C-terminal BTB domains. PoRal2 is involved in sporulation, aerial hypha and conidiophore differentiation, appressorium formation, plant penetration, and virulence. During appressorium formation, ∆Poral2 mutants generate appressoria with long germ tubes on hydrophobic surfaces. ∆Poral2 mutants exhibited a defective response to exogenous cAMP and the activated RAS2G18V on a hydrophilic surface, indicating impairment in the cAMP-PKA or Pmk1 MAPK signaling pathways. Deletion of PoRAL2 leads to lowered Pmk1 phosphorylation level in the mutant. Moreover, PoRal2 is found to interact with Scd1, Smo1, and Mst50, which are involved in activation of Pmk1. In addition, the expression levels of MPG1, WISH, and PDEH in the cAMP-PKA pathway, RAS2 in both the cAMP-PKA and Pmk1 MAPK pathways and melanin biosynthesis genes (ALB1, BUF1, and RSY1) were significantly down-regulated in the ∆Poral2. Therefore, PoRal2 is involved in fungal development and virulence by its crosstalk in the cAMP-PKA and Pmk1 MAPK signaling pathways.